Color Doppler sonography as an adjunct to repeat uterine evacuation for gestational trophoblastic disease: Case report. Issue 1 (28th March 2013) - Tsuyoshi, Hideaki; Sugita, Genki; Kurokawa, Tetsuji; Yoshida, Yoshio
ABSTRACT Repeat uterine evacuation is a therapeutic option for preserving fertility in patients with gestational trophoblastic neoplasms and chemoresistance, but remains controversial due to the risks of hemorrhage and perforation. A 25‐year‐old patient with low‐risk gestational trophoblastic neoplasm became chemoresistant; however, chemotherapy reduced intrauterine tumor vascularity as observed by color Doppler sonography, suggesting that patients could undergo uterine evacuation without major risk of bleeding. After 18 months, she achieved a normal pregnancy. Serial assessment of tumor vascularity with color Doppler sonography may provide information regarding the appropriate time to perform a repeat uterine evacuation without significant bleeding. © 2013 Wiley Periodicals, Inc. J Clin Ultrasound41:54–58, 2013